Sex differences in mass loss rate and growth efficiency in Antarctic fur seal (Arctocephalus gazella) pups at Macquarie Island - Guinet, C; Goldsworthy, SD; Robinson, S (Behavioral Ecology and Sociobiology, 1999)
We investigated the relationship between the mass gained by a pup during a period of maternal attendance (as an index of milk intake) and the duration of the preceding foraging trip in relation to the mass-specific rate of mass loss during fasting periods and the growth rate of Antarctic fur seal (Arctocephalus gazella) pups at Macquarie Island. We found that (1) serially weighed male pups grew significantly faster than females pups and that (2) fasting female pups lost mass at a significantly higher rate (2.55% day-1) than male pups (2.12% day-1) of the same mass; (3) during periods of maternal attendance, there were no intersexual differences in the amount of mass gained by pups of the same size, hence (4) female pups required a higher daily mass gain to grow at the same rate as male pups. Our results show that intersexual differences in growth rate may be accounted for by intersexual differences in mass-specific rate of mass loss, because females lost 0.42% more of their total mass per day (i.e. 4.2 g kg-1 day-1) compared with male pups of the same body mass. Despite intersexual differences in growth rates, our results indicate equality of maternal expenditure between the sexes. Intersexual differences in the rate of mass loss may be due to differences in the metabolic rate, activity level and/or body composition of male and female pups.